Citotaxonomia e evolução cariotípica em bignoiaceae - Cordeiro, Joel Maciel Pereira (2015)
Bignoniaceae is one of the most various families of plants among the Angiosperms, occupying a variety of habitats in the Neotropical and Paleotropical regions. The clade Tabebuia alliance is one of the most representative of the Bignoniaceae with 14 genera and 147 species. In cytogenetic the Bignoniaceae, and consequently the clade Tabebuia alliance, predominate symmetrical karyotypes and small chromosomes, making it difficult to use in citotaxonomy. Although there is the predominance of 2n = 40 chromosomes for most species, there is the record of changes in ploidy level (2n = 80, 120) as well as possible aneuploidy or disploidy (2n = 22, 30, 36, 38) in certain family lineages. This study aimed to establish the citotaxonomy characterization of Neotropical clade Tabebuia alliance, and some related species, with the use of fluorochromes Chromomycin A3 (CMA) and 4'6-diamino-2-phenylindol (DAPI). In addition, chromosome numbers were related with information Molecular phylogeny of data obtained from the chloroplast gene rbcL, and ndhF and non-coding sequence trnL-F for understand the mechanisms involved in karyotypic evolution of clade Tabebuia alliance, well as to the family Bignoniaceae as a whole. 16 species were analyzed, and recorded new scores for Jacaranda jasminoides (2n = 36), Tabebuia elliptica (2n = 40) and Sparatosperma leucanthum (2n = 40). In clade Tabebuia alliance, in species with 2n = 40, there is a predominance of a pair of CMA+ terminal bands and a pair of proximal bands, while polyploid species showed two to three terminal bands and one or two proximal bands per set monoploid. In the species of clades Jacarandeae, Tecomeae and Paleotropical clade analyzed observed the occurrence of small CMA+ terminal bands (J. mimosifolia, J. jasminoides, S. campanulata and P. ricasoliana) and proximal bands (T. stans). Analyses of molecular phylogeny allied with chromosomal counts for the family Bignoniaceae demonstrate that x = 18 would be possibly the ancestral basic number of the family. The species with 2n = 40, 80 and 120 chromosomes from Tabebuia alliance clade derive from an ancestor who would have n = 20. Certain species with 2n = 22, 30, 36, 38 and 42 chromosomes (Tecomeae, argylia, Delostoma) would be part a transition line between basal species with n = 18 (Jacarandeae) and species which have stabilized with n = 20 (Crescentiina, Catalpeae, Bignonieae).